(untitled) (Journal of the College of Basic Education, 2022)
This study deals with the use of local raw materials for the production of ceramic tiles, which are Erdma glass sand and kaolin, and these materials are available in western Iraq. The effect of changing the proportions of kaolin and crack used in the manufacture of tiles has been studied, and the aim of this study is to obtain ceramic tiles with less porosity by obtaining less water absorption. The research included the use of ground glass sand, glass shards, and bentonite, with the proportions remaining constant for each of the mentioned materials